Hematological and biochemical effect of subcutaneous administration of robenacoxib in different goat breeds - Zeynep Ozdemir Kutahya; Petek Piner Benli (Eurasian Journal of Veterinary Sciences, 2023)
Aim: This study aimed to investigate the effect of robenacoxib on hematological and biochemical parameters in healthy Alpine and Saanen goats 24 hours after subcutaneous administration. Materials and Methods: 12 healthy Alpine (n=6) and Saanen (n=6) breed goats were used. Robenacoxib was administered to Alpine and Saanen goats at a dose of 4 mg/kg once subcutaneously. Blood samples were collected before drug administration (0 hour) and then 24-hours. Hematological and biochemical parameters were analyzed using a hematology analyzer and biochemistry auto analyzer, respectively. Results: No change was observed in the clinical examination findings of both goat breeds. Statistical differences in hematological and biochemical parameters were determined within physiological limits in both goat breeds. The white blood cell, red blood cell and lymphocyte values were found to be low, and the monocyte% value was found to be high in Alpine goats. Decreases in red blood cell, hemoglobin and hematocrit levels and increases in the mean corpuscular volume and mean corpuscular hemoglobin values were observed at 24-hours in Saanen goats. Robenacoxib increases blood urea nitrogen value in both goat breeds, it decreases creatinine value in Saanen goats. Conclusion: There were no significant changes in hematological and biochemical parameters after robenacoxib administrations to Alpine and Saanen goats. Consequently, further studies are needed to investigate the effects of robenacoxib in high-dose and repeated administrations, liver and kidney dysfunctions, different age, breed, and physiological conditions. It was evaluated that robenacoxib could be used as an alternative NSAID to prevent pain and inflammation in goats, since no adverse effect was observed in the blood profile.